The impact of COVID-19 on thyroid function and psychological state of Graves’ disease: a one-year prospective study - Xu, Lujia; Zhang, Jianbo; Cong, Riping; Zhang, Yujian; Song, Xuenan; Wang, Wei; Diao, Yingli; Liu, Haijiao; Tang, Kuanxiao (Frontiers in Endocrinology, 2025)
BackgroundSince the comprehensive lifting of coronavirus disease 2019 (COVID-19) pandemic control measures in mainland China in December 2022, the population has experienced widespread infection with COVID-19. COVID-19 affects multiple systems, including the endocrine system, particularly the thyroid. Graves’ disease, a common autoimmune disorder, may be complicated by COVID-19 infection. Therefore, investigating changes in thyroid function and psychological status in patients with Graves’ disease (GDC) and COVID-19 coinfection holds significant clinical importance.MethodsThis study enrolled 110 hyperthyroid patients with COVID-19 coinfection, including 90 GDC patients meeting inclusion criteria. They were prospectively followed for one year at three time points: pre-COVID-19, 3 months, and 1 year post-infection. Patients were categorized by COVID-19 duration: G1 (≤5 days), G2 (6–8 days), and G3 (≥9 days). Follow-up included assessments of COVID-19 and GD symptoms, laboratory tests, psychological evaluations, treatment efficacy, COVID-19 management, and antithyroid medication adjustments. Statistical analyses (rank-sum tests, t-tests, multivariate logistic regression) explored COVID-19-GD associations and changes in thyroid function and psychological status in GDC patients.ResultsMultivariate logistic regression analysis, after covariate adjustment, identified the number of COVID-19 symptoms as an independent risk factor for hyperthyroidism in GDC patients, and COVID-19 duration as an independent risk factor for poor psychological status. At 3 months post-infection, the G3 group showed an increased FT3/FT4 ratio and decreased FT4 levels. Significant intergroup differences were observed in FT4 and TSH changes from pre-infection levels, with the G3 group having the highest anxiety and depression scores. Antithyroid medication and psychological interventions were adjusted based on thyroid function and psychological scores. At 1 year post-infection, TSH levels in the G1 and G3 groups increased compared to 3 months, while psychological scores decreased. The G3 group had significantly higher TSH levels than pre-infection, with significant intergroup differences in FT3 and FT4 levels.ConclusionPost-COVID-19 infection, GDC patients may experience hyperthyroidism and psychological distress, which improve with tailored ATD adjustments and psychological interventions. The FT3/FT4 ratio guides (antithyroid drugs) ATDs optimization, while psychological intervention effectively mitigates anxiety and depression in GDC patients.